Biomarkers of dissolved oxygen stress in oysters: a tool for restoration and management efforts. - Heather K Patterson; Anne Boettcher; Ruth H Carmichael (PLoS ONE, 2014)
The frequency and intensity of anoxic and hypoxic events are increasing worldwide, creating stress on the organisms that inhabit affected waters. To understand the effects of low dissolved oxygen stress on oysters, hatchery-reared oysters were placed in cages and deployed along with continuously recording environmental data sondes at a reef site in Mobile Bay, AL that typically experiences low oxygen conditions. To detect and measure sublethal stress, we measured growth and survival of oysters as well as expression of three biomarkers, heat shock protein 70 (HSP70), hypoxia inducible factor (HIF) and phospho-p38 MAP kinase, in tissues from juvenile and adult oysters. Survival rates were high for both juvenile and adult oysters. Expression levels of each of the 3 isoforms of HSP 70 were negatively correlated to dissolved oxygen (DO) concentrations, suggesting that HSP 70 is useful to quantify sublethal effects of DO stress. Results for HIF and phospho-p38 MAP kinase were inconclusive. Test deployments of oysters to assess expression of HSP 70 relative to environmental conditions will be useful, in addition to measuring abiotic factors, to identify appropriate sites for restoration, particularly to capture negative effects of habitat quality on biota before lethal impacts are incurred.